2017
DOI: 10.26749/rstpp.151.19
|View full text |Cite
|
Sign up to set email alerts
|

The freshwater fauna of the South Polar Region: A 140-year review

Abstract: The metazoan fauna of Antarctic and sub-Antarctic freshwaters is reviewed. Almost 400 species, notably rotifers, tardigrades and crustaceans have been identified. Sponges, molluscs, amphibians, reptiles and fishes are absent though salmonid fishes have been successfully introduced on some of the sub-Antarctic islands. Other alien introductions include insects (Chironomidae) and annelid worms (Oligochaeta). The fauna is predominately benthic in habitat and becomes increasingly depauperate at higher latitudes. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 84 publications
(225 reference statements)
1
29
0
Order By: Relevance
“…The relevance of distance was also revealed by our partial redundancy analysis (which showed that spatial autocorrelation among regions explained a large amount of variance), and it is most likely related to patterns of dispersal. Dispersal among nearby islands occurs mainly via migratory seabirds, which can transport resistant eggs within the gut or in mud adhering to feet 1,6,10,16,17 . Distance among regions is often a key determinant in the distribution of freshwater fauna 18 , which may help explain some inconsistencies in the definition of biogeographic provinces.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The relevance of distance was also revealed by our partial redundancy analysis (which showed that spatial autocorrelation among regions explained a large amount of variance), and it is most likely related to patterns of dispersal. Dispersal among nearby islands occurs mainly via migratory seabirds, which can transport resistant eggs within the gut or in mud adhering to feet 1,6,10,16,17 . Distance among regions is often a key determinant in the distribution of freshwater fauna 18 , which may help explain some inconsistencies in the definition of biogeographic provinces.…”
Section: Discussionmentioning
confidence: 99%
“…We elaborated a presence/absence matrix of all freshwater crustacean species reported for Antarctic and Subantarctic lakes, based on two major literature reviews 6,10 , which contained all the available information to date. We divided each biogeographic province into regions following the above two reviews: CA comprised the En (30°E–90°E), Wi (90°E–150°E) and Sc (150°E–150°W) sectors; MA included the Pa, Ss and So; SA included Sg, Pe, Mc, Hd, Cr and Kr; and SCT included Ca and Ak from New Zealand and Fa from South Atlantic ocean (Table 1, Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fauna is dominated by small ( 200 μm to 5 mm) and inconspicuous invertebrates, usually associated with simple vegetation (lichens, mosses, algae). At least 12 species of Crustacea, including copepods, cladocerans, ostracods, and an anostracan, have been reported from freshwater lakes of the Antarctic continent, Antarctic Peninsula, and the maritime Antarctic South Shetland Islands and South Orkney Islands (Pugh et al 2002;Gibson and Bayly 2007;Dartnall 2017;Diaz et al 2019). There has been a long debate about the origin of the Crustacea that inhabit Antarctic lakes.…”
mentioning
confidence: 99%